2018
DOI: 10.3389/feduc.2018.00050
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Student Motivation in the Linking of Perceived School Climate and Achievement in Reading and Mathematics

Abstract: While the current literature provides valuable insight into how school climate and student motivation impact academic achievement, research examining the mediating effects of motivation in the linking of school climate perceptions and achievement is limited. The current study employed structural equation modeling to examine a model that illustrates the role of self-efficacy and intrinsic motivation in the linking of student perceptions of school climate (teacher/student relationship, order/safety/discipline, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 66 publications
(108 reference statements)
4
22
1
Order By: Relevance
“…Studies that have applied SDT in the education have shown that self-determined motivation is associated with a higher degree of academic adjustment in all levels of schooling. Specifically, autonomous motives are associated with greater academic persistence and better academic performance (Turner et al, 2009;Alivernini and Lucidi, 2011;Gillet et al, 2012;Alivernini et al, 2016;Fan and Williams, 2018). In the university context, Turner et al (2009) found that intrinsic motivation predicted academic performance in undergraduate students enrolled in psychology courses; Ratelle et al (2007), in a study on first-year college students, found that students with high levels of self-determined motivations were more persistent than students with lower levels of self-determined motivation.…”
Section: Self-determination Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Studies that have applied SDT in the education have shown that self-determined motivation is associated with a higher degree of academic adjustment in all levels of schooling. Specifically, autonomous motives are associated with greater academic persistence and better academic performance (Turner et al, 2009;Alivernini and Lucidi, 2011;Gillet et al, 2012;Alivernini et al, 2016;Fan and Williams, 2018). In the university context, Turner et al (2009) found that intrinsic motivation predicted academic performance in undergraduate students enrolled in psychology courses; Ratelle et al (2007), in a study on first-year college students, found that students with high levels of self-determined motivations were more persistent than students with lower levels of self-determined motivation.…”
Section: Self-determination Theorymentioning
confidence: 99%
“…Research has shown that students' motivational resources and competence beliefs in their own capabilities have a central role in predicting academic adjustment outcomes such as academic performance and persistence (Gillet et al, 2012;Fan and Williams, 2018). A theoretical framework that has shown to be valid in studying the process leading to academic adjustment outcomes of students is self-determination theory (SDT, Deci and Ryan, 1985;Ryan and Deci, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent large-sample study of high school students showed that intrinsic motivation mediates the link between perceived school climate (in particular, the teacher-student relationship) and achievement in reading and math (Fan & Williams, 2018). We hoped to replicate these findings using a sample of elementary school children, utilizing the SDT perspective on motivation.…”
Section: Developmental Education and School Climate As External Factomentioning
confidence: 86%
“…2. Building on our own research as well as the work by Fan and Williams (2018), we expected that the developmental education system would have an impact on student motivation, which in turn would be associated with higher grades.…”
Section: Developmental Education and School Climate As External Factomentioning
confidence: 99%